2014
DOI: 10.1242/dmm.015800
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish yolk lipid processing: a tractable tool for the study of vertebrate lipid transport and metabolism

Abstract: Dyslipidemias are a major cause of morbidity and mortality in the world, particularly in developed nations. Investigating lipid and lipoprotein metabolism in experimentally tractable animal models is a crucial step towards understanding and treating human dyslipidemias. The zebrafish, a well-established embryological model, is emerging as a notable system for studies of lipid metabolism. Here, we describe the value of the lecithotrophic, or yolk-metabolizing, stages of the zebrafish as a model for studying lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
100
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(109 citation statements)
references
References 88 publications
(106 reference statements)
7
100
2
Order By: Relevance
“…In accordance, previous studies in avian embryos suggested the CEs at yolk sac become predominant at the near-hatching stage [48, 49]. Notably, a recent study indicated that yolk fatty acids were not actively contributing to CE synthesis until 72 hpf and this contribution could be inhibited by Soat inhibitor [50]. These results and ours indicated that the content and the mechanisms of cholesterol trafficking from the yolk to the embryo may vary along the developmental progress (Fig 10) and the nutrient requirement of the embryos might be very different between initial and later stages of embryogenesis.…”
Section: Discussionsupporting
confidence: 87%
“…In accordance, previous studies in avian embryos suggested the CEs at yolk sac become predominant at the near-hatching stage [48, 49]. Notably, a recent study indicated that yolk fatty acids were not actively contributing to CE synthesis until 72 hpf and this contribution could be inhibited by Soat inhibitor [50]. These results and ours indicated that the content and the mechanisms of cholesterol trafficking from the yolk to the embryo may vary along the developmental progress (Fig 10) and the nutrient requirement of the embryos might be very different between initial and later stages of embryogenesis.…”
Section: Discussionsupporting
confidence: 87%
“…This is consistent with several reports on acyl composition of zebrafish larvae and adults [17,40,56,57]. Most of these studies were based on analyzing the acyl chain components of the different classes after hydrolyzing the phospholipid molecules.…”
Section: Discussionsupporting
confidence: 91%
“…Frequently, these two abnormalities appear together in disturbed embryos, as stated by Oliveira et al (2017). Their occurrence indicates metabolic disturbances in the embryo that prevent the normal use of stored energy in the yolk and cause abnormal accumulations of fluid in the pericardial cavity (Miyares et al, 2014). Also, a series of results in this investigation elucidated the abovementioned adverse effects of DKAs, which are related to the effects of DKAs on energy metabolism and transfer, TEM histopathological observation of adult muscle tissues (especially muscle fiber ablation and swelling of mitochondria), and transcriptional changes in CKma gene.…”
Section: Discussionmentioning
confidence: 95%